Water Energy Harvesting: Flexible Superamphiphobic Film for Water Energy Harvesting (Adv. Mater. Technol. 1/2017). Issue 1 (January 2017) - Lin, Meng‐Fang; Parida, Kaushik; Cheng, Xing; Lee, Pooi See
Abstract : In article number 1600186, Pooi See Lee and co‐workers demonstrate the design of a flexible superamphiphobic SiO2 /poly(vinylidene difluoride‐co‐trifluoroethylene) (PVDF‐TrFE) film to harvest the electrostatic energy from water. The working mechanism of the water‐TENG is based on the triboelectricity generated from the contact electrification between the water and the superamphiphobic SiO2 /P(VDF‐TrFE) film. The flexible superamphiphobic SiO2 /P(VDF‐TrFE) is able to charge a capacitor and to produce energy sufficient to light up the light emitting diodes.